Epistemic Injustice and Its Educational Contexts - Twaróg, Tomasz (INSTED: Interdisciplinary Studies in Education & Society, 2025)
The article presents the concept of epistemic injustice, introduced by Fricker in 2007, and selected social contexts for its occurrence, and then places this concept in the educational field. The purpose of the article is not only to summarize this concept in relation to the two basic types of epistemic injustice: testimonial and hermeneutical injustice, but also to link this issue to the problems of education, and to present proposals for measures to reduce epistemic injustice in educational practice through training in critical thinking and the formation of an attitude of “virtuous hearer.”